Analysis of the Digital Wallet Policy Impacts on the Grassroots Economy and Fiscal Sustainability - Rakphuangthong, Yunyong; Wongwatthanaphong, Kampanart; Ouncharoen, Ratasit; ศรีอาวุธ, วันทนา; Amnuaisin, Ratchadaporn (Journal of MCU Phetchaburi Review, 2025)
This academic article aims to analyze Thailand's "Digital Wallet" policy, implemented in the aftermath of the COVID-19 crisis. The study focuses on the macroeconomic and fiscal context, as well as the short- and long-term impacts on the grassroots economy. With over one trillion baht allocated through various programs such as "Rao Chana," "Khon La Khrueng," "Ying Chai Ying Dai," and the 10,000-baht Digital Wallet project, this initiative represents one of the largest fiscal measures undertaken to stimulate domestic consumption, enhance purchasing power, and mitigate economic hardships, especially for vulnerable populations. The Digital Wallet policy, with a budget of 450 billion baht (PolicyWatch, 2024), seeks to drive large-scale economic revitalization. The analysis finds that the policy has positively impacted local economies by boosting small business incomes and increasing cash flow within communities. However, key limitations are identified, including the risk of long-term dependency on state support, technological barriers in some areas, and concerns over fiscal sustainability due to rising public debt. The article also draws lessons from international experiences in countries like Japan, Taiwan, and China, where similar policies were implemented. It highlights that while cash handouts can stimulate short-term economic activity, poorly designed policies may lead to structural economic issues in the long run. Key policy recommendations include targeting specific groups clearly, continuously evaluating policy outcomes, providing financial literacy education alongside monetary measures, and linking fiscal stimulus to sustainable infrastructure development to maximize economic benefits and minimize fiscal risks over time.